2021
DOI: 10.1186/s12902-021-00762-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlational study on the levels of 25-hydroxyvitamin D and non-alcoholic fatty liver disease in type 2 diabetic patients

Abstract: Background It is widely acknowledged that nonalcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus(T2DM) are all chronic metabolic diseases. The objective of this study is to retrospectively probe the association between the 25-hydroxyvitamin D (25-(OH)D) and NAFLD in type 2 diabetic patients. Methods Three hundred thirty-nine T2DM patients participated in this research and from November 2018 to September 2019 and were divided into sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
4
8
0
Order By: Relevance
“…Visceral obesity, T2DM, dyslipidemia, and arterial hypertension are the phenotypic expression of NAFLD, and the presence of one or more of these conditions increases the risk of developing NAFLD [ 28 ]. In our study, the BMI, SBP, DBP, TG, ALT, AST, GGT, UA, HbA1c, FCP, 2 h CP, HOMA-IR, and HOMA-IS in T2DM patients with NAFLD were significantly higher than those without NAFLD ( P < 0.05), suggesting that T2DM with NAFLD patients are more prone to metabolic abnormalities and insulin resistance, which is consistent with other studies [ 24 , 29 ]. However, there was no significant difference in TC, TG, LDL-C, and H-LDL between the NAFLD and non-NAFLD groups, which may be largely related to the utilization of lipid-lowering drugs in clinical practice impacting the results.…”
Section: Discussionsupporting
confidence: 92%
“…Visceral obesity, T2DM, dyslipidemia, and arterial hypertension are the phenotypic expression of NAFLD, and the presence of one or more of these conditions increases the risk of developing NAFLD [ 28 ]. In our study, the BMI, SBP, DBP, TG, ALT, AST, GGT, UA, HbA1c, FCP, 2 h CP, HOMA-IR, and HOMA-IS in T2DM patients with NAFLD were significantly higher than those without NAFLD ( P < 0.05), suggesting that T2DM with NAFLD patients are more prone to metabolic abnormalities and insulin resistance, which is consistent with other studies [ 24 , 29 ]. However, there was no significant difference in TC, TG, LDL-C, and H-LDL between the NAFLD and non-NAFLD groups, which may be largely related to the utilization of lipid-lowering drugs in clinical practice impacting the results.…”
Section: Discussionsupporting
confidence: 92%
“…Nutraceuticals with hypoglycemic and anti‐lipidemic properties alongside antioxidative and anti‐inflammatory actions have emerged as potential therapies for MAFLD since FDA‐approved drugs are lacking 19,20 . Under this theme, several epidemiological studies have shown that serum 25‐OH VD levels correlated negatively with obesity, insulin resistance and severity of MAFLD 29,30 . Moreover, VD deficiency in mice upregulated the expression of hepatic lipogenic molecules, including PPAR‐γ and SREBP1, decreased PPAR‐α and β‐oxidation as well as resulted in dyslipidemia and insulin resistance 31 .…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Under this theme, several epidemiological studies have shown that serum 25-OH VD levels correlated negatively with obesity, insulin resistance and severity of MAFLD. 29,30 Moreover, VD deficiency in mice upregulated the expression of hepatic lipogenic molecules, including PPAR-γ and SREBP1, decreased PPAR-α and β-oxidation as well as resulted in dyslipidemia and insulin resistance. 31 In contrast, VD 3 therapy reduced obesity, enhanced insulin sensitivity, modulated hepatic lipid metabolizing molecules, and mitigated inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations